Tumor aneuploidy correlates with hallmarks of cancer - Danielsen, Håvard E.; Hveem, Tarjei S.; Liestøl, Knut (Journal of Laboratory and Precision Medicine, 2017)
Abnormalities of cellular DNA content have long been associated with tumorigenesis. Such abnormalities were originally implicated in cancer development over 100 years ago by German biologist Boveri (1), and during the last years it has become clear that cellular aneuploidy is a driving force in the process of carcinogenesis.